Right lobe living donor liver transplantation – experience from the Department of Hepatobiliary Surgery - K. O. Semash; T. A. Dzhanbekov (Вестник трансплантологии и искусственных органов, 2025)
Background. Living-donor liver transplant (LDLT) is a life-saving procedure for patients with end-stage liver diseases. Objective: to evaluate the outcomes of the first independent LDLT performed at the Department of Hepatobiliary Surgery, Vakhidov Republican Specialized Surgical Research and Practical Medical Center of Surgery, and to demonstrate that liver transplantation (LT) is a feasible procedure at our institution.Materials and methods. From October 2021 to December 2023, 40 right lobe LDLTs were performed in our department. Short-term and long-term outcomes in recipients were assessed. The outcomes of transplant hepatectomy were also evaluated.Results. Hepatic artery thrombosis developed in 1 case (2.5%); arterial anastomotic stenosis was detected in 3 cases (7.5%), which were repaired by endovascular balloon dilation; splenic artery steal syndrome was diagnosed in 3 cases (7.5%), which was resolved by endovascular splenic artery embolization. One patient (2.5%) developed portal vein thrombosis. Two patients (5%) had portal vein stenosis 10 months after transplantation; endovascular balloon angioplasty was performed with good clinical effect. Biliary complications accounted for 45%, of which 89% were biliary leaks and 11% were anastomotic biliary stricture. In-hospital mortality was 12.5%.Conclusion. The results of our experience and analysis of post-transplant complications are comparable with those of the world literature and are acceptable at the stage of implementation of the LT program. Transplantation is feasible at our center, but it is necessary to improve surgical and conservative treatment techniques in order to minimize early and late postoperative complications.